Mitotic slippage: an old tale with a new twist. Issue 1 (2nd January 2019) - Sinha, Debottam; Duijf, Pascal H.G.; Khanna, Kum Kum
ABSTRACT: Targeting the mitotic machinery using anti-mitotic drugs for elimination of cancer cells is a century-old concept, which continues to be routinely used as a first line of treatment in the clinic. However, patient response remains unpredictable and drug resistance limits effectiveness of these drugs. Cancer cells exit from drug-induced mitotic arrest (mitotic slippage) to avoid subsequent cell death which is thought to be a major mechanism contributing to this resistance. The tumor cells that acquire resistance to anti-mitotic drugs have chromosomal instability (CIN) and are often aneuploid. In this review, we outline the key mechanisms involved in dictating the cell fate during perturbed mitosis and how these processes impede the efficacy of anti-mitotic therapies. Further, we emphasize the recent work from our laboratory, which highlights the functional role of CEP55 in protecting aneuploid cells from death. We also discuss the rationale of targeting CEP55 in vivo, which could prove to be a novel and effective therapeutic strategy for sensitizing cells to microtubule inhibitors and might offer significantly improved patient outcome. Abbreviations : APC/C: Anaphase-Promoting Complex/Cyclosome; BAD: BCL2‐Associated agonist of cell Death; BAK1: BCL2 Antagonist Kinase1; BAX: BCL2‐Associated X; BCL2: B-cell Chronic Lymphocytic Leukaemia (CLL)/Lymphoma 2; BH: BCL2 Homology Domain; BID: BH3‐Interacting domain Death agonist; BIM: BCL2‐Interacting Mediator of cell death; BUB: Budding Uninhibited by Benzimidazoles; CDC: Cell Division Cycle; CDH1: Cadherin-1; CDK1: Cyclin-Dependent Kinase 1; CEP55: Centrosomal Protein (55 KDa): CIN: Chromosomal Instability; CTA: Cancer Testis Antigen; EGR1: Early Growth Response protein 1; ERK: Extracellular Signal-Regulated Kinase; ESCRT: Endosomal Sorting Complexes Required for Transport; GIN: Genomic Instability; MAD2: Mitotic Arrest Deficient 2; MCL1: Myeloid Cell Leukemia sequence 1; MPS1: Monopolar Spindle 1 Kinase; MYT1: MYelin Transcription factor 1; PLK1: Polo Like Kinase 1; PUMA: p53-Upregulated Mediator of Apoptosis; SAC: Spindle Assembly Checkpoint; TAA: Tumor-Associated Antigen